Estrategias didácticas innovadoras para motivar la participación activa de los estudiantes en el proceso enseñanza aprendizaje de Ciencias Naturales. Año lectivo 2023-2024. - Nicolalde Sarango, Scarleth Yanela (2024)
The aplication of innovative didactic strategies in the development of the teaching-learning process is important; these motivate students to actively participate in this process, which enhances their academic performance. The objective of this research was: << To enhance the academic performance of students through the implementation of innovative didactic strategies that motivate their interest in participating in the teaching-learning process of Natural Sciences of the tenth year of GBE, of "Adolfo Valarezo" Educative Unit, academic year 2023- 2024>>. The method used was inductive; through direct observation, the problem was identified and information was searched in order to propose actions to improve the identified reality; the approach was qualitative; relevant characteristics of the teaching-learning process were identified, such as: the lack of implementation of innovative teaching strategies and the disinterest of students to participate, which results in low academic performance. As for the type of research, this corresponds to Participatory Action Research; since, during the implementation of the intervention proposal, both the student researcher and the students assumed an active role to solve the identified problem. In addition, according to the temporality it is transversal; because, from the diagnosis, the development of the intervention proposal and the analysis of results, corresponded to a relatively short period of time. Among the main results, it was determined that strategies such as: Gamification, discovery learning, experimentation and visual thinking, motivated students to actively participate in the development of the TLP and therefore their academic performance was enhanced. It is concluded that the academic performance of students is enhanced by motivating their interest to actively participate in the teaching and learning process of Natural Sciences through the implementation of innovative didactic strategies in the development of this process. Key words: Educational innovation, academic achievement, learning construction, didactic techniques.